Critical parameters of a sprint start and acceleration phase - Gouvali, M.; Boudolos, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The sprint start and acceleration phase are determining factors of the final result of a sprint running race (Coh et al. 1998). The purpose of the present study was to identify the most critical parameters of the `set` position and the pushing phase of a sprint start, as well as to determine the relationship between those and the maximum velocity (Vmax) at the initial acceleration phase (0-10m).